Factors affecting customer's decision in using Tabung Haji ATM services: a case study in Tabung Haji headquarter, Kuala Lumpur / Sulisa Supardi - Supardi, Sulisa (Faculty of Business Management, 2017)
The aim of this research is to examine the factors that may affect customer's decision in using Tabung Haji ATM services. This study is conducted in order to know whether Tabung Haji customers in Kuala Lumpur accept its ATM services offered. In order to explain the major factor of customer's decision in using Tabung Haji ATMs, this research includes four independent variables which are credibility (CR), ease of use (EOU), and usefulness (USE). To carry out this study, 150 copies of a structured questionnaire will be distributed to the Tabung Haji customers to see the feedback from respondents regarding this ATM facility. Various statistical tools and tests such as descriptive analysis, multiple regression, correlation and ANOVA are used for collected data accurately. It was analysed by using Statistical Packaged for Social Science (SPSS) Version 2.1. This study suffers from three limitations which are lack of experience, time constraint and sample of study. Nevertheless, these limitations provide directions for future study and also give new information in financial innovation of Tabung Haji. The previous study also reveals that all independent variable between credibility, ease of use and usefulness have significant relationship with dependent variable which is customer's decision. This research provide evidence for management in banking industry services to know the services of ATM facilitates services in Islamic bank for the purpose better providing customer service.